Pendidikan Karakter Dalam Perspektif Profetik - Wahyu Ningsih; Nauval fadlan subarkah (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Prophetic education refers to the prophetic mission, namely perfecting morals and bringing love to the universe. Apart from that, prophetic social ethics also refers to the four characteristics of the prophet, namely shiddiq (honesty), amanah (educated and responsible), fathonah (wise and wise), tabhlig (conveying the truth), this shows that prophetic education requires a person who millennials who are tolerant, compassionate and counter radicalism. Education is not only about academic ability but also the ability to know oneself. Prophetic education makes individuals become human beings who contribute well. By implementing prophetic education, we hope that prophetic education can become a reference in character education. As the Prophet has exemplified the character of every human being, this can be used as an example for educators in implementing character education from a prophetic perspective.